Liquid-based Cytology (LBC) Method for Gynecologic Cytology - Sari, Lenny (Indonesian Journal of Cancer, 2010)
Liquid-based Cytology (LBC) Method for Gynecologic CytologyÂ Full text : http://www.scribd.com/doc/43597706/Liquid-based-Cytology-LBC-Method-for-Gynecologic-Cytology